Effects of an emotional intelligence training program on alleviating internet addiction of college students at the risk of internet addiction in China - Chunlin Yao; Yan Zhang; Haili Hou (Acta Psychologica, 2025)
This research investigates the impact of an emotional intelligence training program on reducing internet addiction among college students identified as at risk for this condition in China. The study employs an experimental design featuring pre-test, post-test, and after-test phases. A sample of 87 students exhibiting signs of internet addiction was selected for the study. Based on pre-test outcomes, participants were randomly assigned to either an experimental group or a control group. Both groups received instruction from the same educator using identical methodologies. However, the experimental group underwent an 11-week emotional intelligence training program. Assessments of emotional intelligence and internet addiction were conducted again at the 12th and 32nd weeks (post-test and after-test, respectively). Analysis of the data indicated that the experimental group exhibited significantly higher mean scores in emotional intelligence (87.45 vs. 82.56, p = 0.003 < 0.01, Cohen's d = −0.666, medium effect; 87.30 vs. 82.67, p = 0.004 < 0.01, Cohen's d = −0.629, medium effect) and significantly lower mean scores in internet addiction (51.61 vs. 54.58, p = 0.014 < 0.05, Cohen's d = 0.536, medium effect; 51.95 vs. 54.72, p = 0.024 < 0.05, Cohen's d = 0.491, small effect) compared to the control group. Furthermore, a negative correlation was observed between the mean scores of internet addiction and emotional intelligence across all testing phases (r values of −0.956, −0.920, and − 0.929 for pre-test, post-test, and after-test, respectively). The findings suggest that the emotional intelligence training program implemented in this study significantly enhances emotional intelligence and reduces internet addiction among college students at risk of internet addiction in China.